Burials, migration and identity in the ancient Sahara and beyond - Gatto, Maria Carmela; Mattingly, D. J. 1958-; Ray, Nick; Sterry, Martin ca. 20./21. Jh (Cambridge University Press, 2019)
"This ground-breaking volume explores a series of inter-related key themes in Saharan archaeology and history. Migration and identity formation can both be approached from the perspective of funerary archaeology, using the combined evidence of burial structures, specific rites and funerary material culture, and integrated methods of skeletal analysis including morphometrics, palaeopathology and isotopes. Burial traditions from various parts of the Sahara are compared and contrasted with those of the Nile Valley, the Maghreb and West Africa. Several chapters deal with the related evidence of human migration derived from linguistic study. The volume presents the state of the field of funerary archaeology in the Sahara and its neighbouring regions and sets the agenda for future research on mobility, migration and identity. It will be a seminal reference point for Mediterranean and African archaeologists, historians and anthropologists as well as archaeologists interested in burial and migration more broadly"...
Keywords: Funeral rites and ceremonies -- Africa, North; Archaeology -- Africa, North; Africa, North -- Emigration and immigration -- History; Aufsatzsammlung